A Novel In Vitro Primary Human Alveolar Model (AlveolAir™) for H1N1 and SARS-CoV-2 Infection and Antiviral Screening - Cindia Ferreira Lopes; Emilie Laurent; Mireille Caul-Futy; Julia Dubois; Chloé Mialon; Caroline Chojnacki; Edouard Sage; Bernadett Boda; Song Huang; Manuel Rosa-Calatrava; Samuel Constant (Microorganisms)
Lower respiratory infections, mostly caused by viral or bacterial pathogens, remain a leading global cause of mortality. The differences between animal models and humans contribute to inefficiencies in drug development, highlighting the need for more relevant and predictive, non-animal models. In this context, AlveolAir™, a fully primary in vitro 3D human alveolar model, was characterized and demonstrated the sustained presence of alveolar type I (ATI) and type II (ATII) cells. This model exhibited a functional barrier over a 30-day period, evidenced by high transepithelial electrical resistance (TEER). These findings were further validated by tight junctions’ confocal microscopy and low permeability to Lucifer yellow, confirming AlveolAir™ as robust platform for drug transport assays. Additionally, successful infections with H1N1 and SARS-CoV-2 viruses were achieved, and antiviral treatments with Baloxavir and Remdesivir, respectively, effectively reduced viral replication. Interestingly, both viruses infected only the epithelial layer without replicating in endothelial cells. These findings indicate AlveolAir™ as a relevant model for assessing the toxicity and permeability of xenobiotics and evaluating the efficacy of novel antiviral therapies.